DASAR LEGALITAS PEREDARAN MINUMAN BERALKOHOL TRADISIONAL JENIS SOPIA DI WILAYAH NUSA TENGGARA TIMUR - Dari, Damianus Ngere; Tuba Helan, Yohanes G; Yohanes, Saryono (Petitum Law Journal, 2023)
Local alcoholic drinks or commonly known as sopi have never been separated from the culture of the people of East Nusa Tenggara. Sopi, apart from being used for consumption, also always colors religious celebrations in East Nusa Tenggara, such as proposals, weddings and traditional ceremonies. However, the distribution of alcoholic drinks that are not based on applicable regulations will have a negative impact on social problems, such as an increase in crime. The East Nusa Tenggara Provincial Government has a program to legalize local alcohol drinks in NUSA TENGGARA TIMUR. In this legalization, the Governor of NUSA TENGGARA TIMUR issued Governor's Regulation Number 44 of 2019 concerning Purification and Management of Traditional Alcoholic Drinks. It is hoped that this governor's regulation can create a reasonable balance between maintaining public health and preserving traditions, as well as supporting the livelihoods of the people in NUSA TENGGARA TIMUR province.